Management of bilateral pterygoid myositis ossificans-like lesion in dogs - De Paolo, Mercedes; Gracis, Margherita; Lacava, Giuseppe; Vapniarsky, Natalia; Arzi, Boaz (Frontiers in Veterinary Science, 2022)
Myositis ossificans (MO) and myositis ossificans-like lesions have been rarely described within the veterinary literature, and are even less common in the maxillofacial region. When MO affects the muscles of mastication, it can result in complete or partial inability to open the mouth. As with other conditions resulting in decreased or restricted mandibular range of motion, severe and potentially fatal sequelae such as difficulty with prehension, swallowing, and air exchange are possible. Diagnostic imaging is essential in achieving an accurate diagnosis and in formulating an appropriate treatment plan. In this ‘method’ manuscript, we provide a detailed description of our approach to diagnosis and surgical management of MO-like lesions of the pterygoid muscles and describe our experience with two young French bulldogs.